Modelling Work–Study Conflict Effects on Built Environment Students’ Well-Being, Health, and Academic Performance - Marini Samaratunga; Imriyas Kamardeen (Buildings)
Balancing academic responsibilities and work commitments poses significant challenges for students in built environment (BE) programs, often leading to compromised well-being and academic difficulties. This study examines the causal effects of balancing work–study responsibilities on students’ health, well-being, and academic outcomes, addressing critical gaps in the literature. A positivist research approach was employed, with data collected via an online survey of 253 undergraduate BE students from Australian universities. The survey assessed academic and work stressors, health, mental well-being, coping strategies, and academic outcomes. Statistical analyses, including one-sample t-tests, factor analysis, and path analysis, were used to analyse the data. The findings reveal that BE students experience severe stress and moderate levels of anxiety and depression, significantly impacting their academic performance. Common health issues include fatigue and sleep disturbances. Work–study conflict and performance anxiety were identified as the strongest predictors of negative health outcomes, with maladaptive coping strategies amplifying these effects. These results underscore the urgent need for institutional interventions, such as flexible learning options, enhanced mental health services, and industry partnerships to alleviate work–study conflicts. Encouraging adaptive coping mechanisms and providing targeted support can help mitigate adverse effects, promoting improved academic performance and well-being among BE students. These findings can be generalised to students in other academic disciplines and countries, as similar work–study challenges and their associated impacts are observed globally.